f(x) | = | 1 ------ (2x-4) |
Rad | degrees | sin | cos |
0π | 0 | 0 | 1 |
1/6π | 30 | 1/2 | 1/2 √ 3 |
1/4π | 45 | 1/√2 | 1/√2 |
1/3π | 60 | 1/2 √3 | 1/2 |
1/2π | 90 | 1 | 0 |
f(x) | = | 1 ------ (3x-5) |
f(x) | = | (3x+7) ------- (3x-2) |
f(x) | = | (3x+7) ------- (3x-2) |
= | (3x-2+9) --------- (3x-2) |
= | 1+ | 9 ----- (3x-2) |
f(x) | = | (2x+6) ------- (x+4) |
f(x) | = | (2x+6) ------- (x+4) |
= | 2 | (x+3) --------- (x+4) |
= | 2 | (x+4-1) ----- (x+4) |
= | 2 | ( | 1+ | -1 ----- (x+4) |
) | = | 2 | + | -2 ----- (x+4) |
f(x) | = | 4x^{4}+4x^{3}+x^{2}+3 ---------------- 2x+1 |
f(x) | = | 4x^{4}+4x^{3}+x^{2}+3 ---------------- 2x+1 |
= | 2x^{3}+x^{2}+x+ | 3 ---- 2x+1 |
∫f(x)dx | = | ∫ ( | 4x^{4}+4x^{3}+x^{2}+3 ---------------- 2x+1 |
) dx | = | ∫ ( | 2x^{3}+x^{2}+x+ | 3 ---- 2x+1 |
) dx |
f(x) | = | x -------- dx (1+x^{2})^{3} |
∫f(x)dx | = | ∫ | x^{2}+3 -------- dx 2x |
∫ f(x)dx | = | ∫ | x^{2}+3 -------- dx 2x |
= | ∫ | x^{2} --- dx 2x |
+ | ∫ | 3 --- dx 2x |
F(x) | = | 1 ---- ln(a) |
a^{x} + C |